To simplify the expression \( 4\sqrt{3} + 2\sqrt{48} \), we start by simplifying \( \sqrt{48} \).
-
Simplify \( \sqrt{48} \): \[ \sqrt{48} = \sqrt{16 \times 3} = \sqrt{16} \times \sqrt{3} = 4\sqrt{3} \]
-
Substitute back into the original expression: Now replace \( \sqrt{48} \) in the original expression: \[ 2\sqrt{48} = 2(4\sqrt{3}) = 8\sqrt{3} \]
-
Combine the terms: Now we can combine: \[ 4\sqrt{3} + 8\sqrt{3} = (4 + 8)\sqrt{3} = 12\sqrt{3} \]
The final answer in simplest radical form is: \[ \boxed{12\sqrt{3}} \]